Perceived organizational culture and its relationship with job satisfaction in primary hospitals of Jimma zone and Jimma town administration, correlational study - Dereje Mesfin; Mirkuzie Woldie; Ayinengida Adamu; Fitsum Bekele (BMC, 2020)
Abstract Background The concept of Organizational Culture (OC) which refers to the pattern of values, norms, beliefs, attitudes and assumptions may not be articulated through verbal language. However, it shapes the way people behave and the way things get done in an organization. The management of organizational culture is increasingly viewed as necessary part of health system reform. Major cultural transformation of an organization must be secured alongside structural and procedural changes in order to achieve desired quality and performances improvements in health systems. It is therefore essential to understand organizational culture, job satisfaction level of the health workers and the link between them. Methodology Facility based cross sectional study was conducted in four primary hospitals of Jimma zone and town administration. A self-administered questionnaire was used to collect the data. The collected data were checked for completeness, entered and documented into Epi-data version 3.1 and Exported to SPSS version 21 for analysis. Finally descriptive statistics, Paired t-test and multiple linear regression analysis were used to assess the relationship between organizational culture and job satisfaction and the results were presented using tables and charts. Result It was indicated from the finding that, the dominant existing organizational culture typology in the primary hospitals was Hierarchy culture (MS = 22.31, ±2.82).and the preferred organizational culture typology was Innovative culture (MS = 26.09, ±4.72). The health workers had low to medium level of job satisfaction where only (29.40%) of the health workers were very satisfied with their hospital physical working environment. Existing perceived clan culture had positive and significant correlation with health workers' satisfaction in relation to work relation dimension (r = .16, p < 0.002). Conclusion while acknowledging all limitation of observational study we reached to the conclusion that an employees of the respective primary hospitals would prefer to work in environment characterized by innovative and clan culture and their satisfaction level is medium so that the managers should undertake major cultural transformation and must work to improve the job satisfaction level of health workers within their respective hospitals.